SNS <고독방>의 커뮤니케이션 양상 연구: 익명성이 보장된 공간에서 이미지로 대화하기 - 배소연(Bae So-Yon), 권순희(Kwon Soon Hee) (교과교육학연구, 2020)
지인들과 연락하기 위한 도구로 사용되는 카카오톡이, 최근 들어서는 익명의 사람들과 공통의 관심사를 공유하는 수단으로도 사용되고 있다. 본 연구는 텍스트를 일체 사용하지 않고 이미지만을 가지고 소통하는 카카오톡 오픈채팅 ‘고독방’의 대화 양상과 이용자들의 소통 심리를 살펴보고, 이것이 우리의 일상 커뮤니케이션에 어떠한 영향을 미치는지 밝히고자 하였다. 이를 위해 연구자가 직접 고독방 대화에 참여하여 관찰한 후, 고독방 이용 경험이 있는 사람을 대상으로 온라인 설문 조사를 진행하였다. 고독방 대화는 기존 텍스트 대화와 마찬가지로 다수의 정보가 공유되었으며, 이 과정에서 본인이 하고 싶은 말만 일방적으로 전달하는 집단적 독백 형태가 나타났다. 반면 익명임에도 불구하고 공손한 태도를 보였는데, 이는 공통의 관심사를 가진 참여자들 간에 유대감과 연대감이 강하게 형성된 결과라 생각해 볼 수 있다. 텍스트가 아닌 이미지 중심의 소통이 선호되고 있는 가운데, 국어교육에서 시각적 서사 학습, 이미지 리터러시 교육 등 읽기를 넘어 보기에 대한 교육을 통해 상호작용과 공감 소통하는 학습 방식이 논의되어야 할 것이다. Kakao Talk, the social media channel to communicate with acquaintances, began to be used as a means of sharing common interests with anonymous people. The study looked at the dialogue patterns of Kakao Talk open chat “Solitude Room” where they communicates only with images without any text, and tried to reveal how this affected our daily communication. The researchers participated in the “Solitude Room” and observed the dialogue and conducted an online survey of people with experience of using the “Solitude Room”. Just like traditional text conversations, in “Solitude Room” a large amount of information was shared, and in the process, a collective monologue emerged, for one-way communication, conveying only what one would like to say. On the other hand, while remaining anonymous, they showed a polite attitude, and this seemed to be due to strong bond and solidarity among participants of common interest. While image-oriented communication rather than text is preferred, it will be necessary to discuss how to interact with and empathize the interaction through education on viewing such as visual narrative learning and image literacy education, going beyond reading in Korean language education. KCI Citation Count: 0